Medium adaptive air-sea cross-domain photoelectric composite umbilical cable
Patent Information
- Application Number
- CN202611208363.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-11
AI Technical Summary
[0009]本申请针对现有光电复合脐带缆仅适用于单一服役环境,难以同时适应海水与空气两种介质在密度、静压、温度及腐蚀机制方面存在的数量级差异,致使跨介质使用时存在浮力失配、光电性能衰减等问题,本申请提供了一种由内至外依次包括光电功能单元、承力层、防水内护套、可逆浮力调控层、微孔透水膜及梯度可渗水外护套的光电复合脐带缆
1、本申请通过采用氟硅氧烷改性热塑性聚氨酯梯度外护套,在挤出成型及冷却过程中,利用氟硅氧烷链段与热塑性聚氨酯基体之间的热力学不相容性,氟硅氧烷链段自发向熔体-空气界面迁移富集,形成外层富集氟硅氧烷链段、内层富集热塑性聚氨酯基体的径向梯度结构。基于该梯度结构,外护套外层表面能降低,使得外护套具有良好的疏水、疏油及防污性能,有效减少海洋生物附着,减少外护套外表面携水;同时,外层富集的硅氧烷链段利用其非碳主链结构及表面惰性氧化硅层的形成,提高耐氧化性,从而增强外护套在盐雾环境下的耐腐蚀性能,并在空气环境中有效抵抗强紫外辐射及臭氧侵蚀,延缓传统热塑性聚氨酯护套在跨介质回收后出现的老化、粉化现象。内层富集的热塑性聚氨酯基体自身保持良好的柔韧性、高弹性及与下层材料的良好粘结性,有效避免因整体氟硅化导致的外护套硬度增加及层间剥离风险,确保外护套在反复出入水、卷绕布放等复杂工况下不因表面硬化而开裂,维持稳定的密封性能与机械完整性。实现了海水-空气跨介质环境中疏水耐蚀、耐紫外臭氧老化及宽温域力学稳定性。
Smart Images

Figure CN122739018B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of optoelectronic composite cable technology, and in particular to a medium-adaptive air-sea cross-domain optoelectronic composite umbilical cable. Background Technology
[0002] As the core transmission channel connecting surface / air platforms and underwater equipment, umbilical cables must simultaneously provide power supply, optical signal transmission, and mechanical load-bearing functions. Currently, relatively mature product systems have been developed for single service environments.
[0003] For example, existing technology 1 discloses a permeable, high-strength, zero-buoyancy, waterproof optoelectronic composite umbilical cable that achieves deep-sea levitation through a permeable outer sheath membrane and a glass microsphere density adjustment layer. However, this design is based on continuous immersion in water. Once the cable is exposed to air, the water trapped in the glass microsphere layer cannot be actively expelled, leading to a sharp increase in the cable's linear density and a deterioration in its bending stiffness. Furthermore, the outer sheath membrane lacks resistance to ultraviolet radiation and ozone aging, making it difficult to adapt to alternating air and sea environments.
[0004] Existing technology 2 discloses a wide-temperature-range optical-electric composite cable for aerospace applications, which achieves a wide temperature range of -200℃ to +260℃ by using MLI heat insulation film, Kevlar insulation layer and PFA filler. However, this structure is optimized for vacuum and radiation environments, lacks the ability to adapt to seawater permeation pressure, and also lacks salt spray corrosion protection design, so it cannot be directly applied to marine environments.
[0005] The three existing technologies focus on cross-medium communication methods, using thin-diameter optical cables and photoacoustic conversion to achieve air and sea information transmission, but do not address the structural integrity, sealing reliability, and photoelectric performance stability of the cable itself during the medium switching process.
[0006] From a materials and structural perspective, seawater and air are two media with similar densities (seawater is approximately 1.025 g / cm³). 3 Air is approximately 0.0012 g / cm³. 3 ), static pressure (tens of MPa in the deep sea, atmospheric pressure in the air), temperature (2-4℃ in the deep sea, -50℃ to +60℃ and above in the high air), and corrosion mechanism (seawater salt spray Cl). - There are orders of magnitude differences in pitting corrosion and air UV / ozone aging. Traditional umbilical cables, if performing cross-medium tasks, will face the following prominent problems: Sealing fatigue contradiction: The extruded sheath is over-compressed under the high pressure of the deep sea. After exiting the water, the pressure drops sharply, resulting in insufficient elastic rebound. Repeated water entry and exit cause micro-motion wear at the sealing interface, which eventually leads to leakage. Buoyancy mismatch contradiction: The underwater zero buoyancy design relies on water absorption to increase weight or microbead drainage. After surfacing, the residual water cannot be discharged in time, and the cable body suddenly changes from zero buoyancy to a large load, which seriously restricts aerial deployment and recovery. The contradiction of photoelectric performance degradation: optical fibers are prone to micro-bending loss in pressure-temperature coupled fields, and the dielectric properties of cable insulation degrade under alternating dry and wet conditions. Existing buffer materials are difficult to meet the dual requirements of deep-sea pressure resistance and air kink resistance at the same time. The contradiction of load-bearing layer corrosion: Traditional galvanized steel wire armor is simultaneously subjected to Cl in alternating salt spray and atmospheric corrosion environments. - Pitting and galvanic corrosion, coupled with the high density of the steel wire, further exacerbate the load problem after the water is discharged.
[0007] In the future, underwater vehicles will be equipped with aircraft and connected by umbilical cables to achieve purposes such as information relay and signal detection. The cross-medium umbilical cable needs to be able to be used in both seawater and air.
[0008] Therefore, there is an urgent need for a new optical-electric composite umbilical cable structure that can actively adapt to changes in the medium and achieve a smooth performance transition between seawater and air. Summary of the Invention
[0009] This application addresses the limitations of existing optoelectronic composite umbilical cables, which are only suitable for a single service environment and cannot simultaneously adapt to the orders-of-magnitude differences in density, static pressure, temperature, and corrosion mechanisms between seawater and air. This leads to problems such as buoyancy mismatch and photoelectric performance degradation when used across media. This application provides an optoelectronic composite umbilical cable comprising, from the inside out, a photoelectric functional unit, a load-bearing layer, a waterproof inner sheath, a reversible buoyancy control layer, a microporous permeable membrane, and a gradient permeable outer sheath. The outermost layer of the cable is a gradient sheath made of fluorosiloxane-modified thermoplastic polyurethane. During extrusion molding and cooling, fluorosiloxane segments spontaneously migrate and enrich towards the outer layer, forming a radial gradient structure where the outer layer is enriched with fluorosiloxane segments and the inner layer is enriched with thermoplastic polyurethane matrix. The outer layer provides hydrophobicity and salt spray corrosion resistance in seawater environments and UV and ozone aging resistance in air environments, while the inner layer provides mechanical protection, achieving a synergy between cross-media environmental adaptability and mechanical performance. Meanwhile, the reversible buoyancy control layer is composed of closed-cell hollow glass microspheres, semi-open-cell polyurethane foam particles, and temperature-sensitive superabsorbent polymer (SAP). The semi-open-cell polyurethane foam particles provide physical water storage and drainage, the temperature-sensitive SAP provides temperature-responsive chemical regulation and water-blocking, and the closed-cell hollow glass microspheres provide skeletal support and basic buoyancy. These three components work together to achieve reversible control of the cable density during seawater-air medium switching, overcoming the shortcomings of traditional glass microsphere density adjustment layers, such as unidirectional water absorption, inability to actively drain water, and residual water retention after discharge leading to aerial load. The specific technical solution provided in this application is as follows: This application provides a medium-adaptive air-sea cross-domain optoelectronic composite umbilical cable, which includes, from the inside out: optoelectronic functional unit, load-bearing layer, waterproof inner sheath, reversible buoyancy control layer, microporous water-permeable membrane and gradient water-permeable outer sheath. The gradient permeable outer sheath is the outermost structure of the cable body; the microporous permeable membrane is attached to the inner wall of the gradient permeable outer sheath; the reversible buoyancy control layer is filled in the annular cavity formed by the microporous permeable membrane and the waterproof inner sheath. The gradient permeable outer sheath is a fluorosiloxane-modified thermoplastic polyurethane gradient sheath, which is made by melt reaction extrusion granulation of thermoplastic polyurethane granules, fluorosiloxane oligomers and crosslinking / grafting agents, followed by extrusion molding. The reversible buoyancy control layer includes closed-cell hollow glass microspheres, polyurethane semi-open-cell foam particles, and temperature-sensitive superabsorbent resin.
[0010] In some preferred embodiments, the gradient permeable outer sheath is made by melt reaction extrusion granulation of polyether thermoplastic polyurethane granules, hydroxyl-terminated fluorosilicone oil and polyisocyanate in a mass ratio of 100:5~15:0.5~2, followed by extrusion molding. The molecular weight of the hydroxyl-terminated fluorosilicone oil is 1000~5000.
[0011] In some preferred embodiments, the closed-cell hollow glass microspheres are soda-lime borosilicate-based hollow glass microspheres with a true density of 0.19~0.24 g / cm³. 3 The particle size D50 is 45~78μm, the compressive strength is ≥5.0MPa, and the volume content is 25%~40% of the total volume of the reversible buoyancy control layer; The polyurethane semi-open-cell foam particles are based on a polyether-type polyurethane matrix and have a semi-open-cell structure with a pore size of 300~800μm, an open-cell ratio of 60%~75%, and a density of 0.06~0.12g / cm³. 3 The compressive strength is ≥1.0MPa, the compression set is ≤8%, the resilience is ≥50%, and the volume content is 35%~55% of the total volume of the reversible buoyancy control layer; The temperature-sensitive superabsorbent resin is a poly(N-isopropylacrylamide) crosslinked modified sodium polyacrylate superabsorbent gel with a low critical dissolution temperature of 28-32°C, a dry particle size of 100-200 μm, and a mass content of 3-8% of the total mass of the reversible buoyancy control layer.
[0012] In some preferred embodiments, the microporous permeable membrane is a pressure-resistant composite microporous membrane, comprising an inner microporous membrane and an outer high-strength polyester fiber woven reinforcing mesh. The inner microporous membrane is made of expanded polytetrafluoroethylene or thermoplastic polyurethane. The overall thickness of the microporous permeable membrane is 0.20~0.35mm, and it can withstand hydrostatic pressure ≥1.0MPa. The pore size of the inner microporous membrane is 0.3~2.0μm, and the porosity is 70%~80%.
[0013] In some preferred embodiments, the waterproof inner sheath is made of polyether-type thermoplastic polyurethane or polyethylene material, with a thickness of 0.6~1.0 mm, a Shore hardness of A85~95, and a permeability coefficient of less than 1×10⁻⁶. -12 cm 3 ·cm / (cm 2 ·s·Pa).
[0014] In some preferred embodiments, the inner wall of the annular cavity is provided with a longitudinal water guide groove extending along the axial direction of the cable body.
[0015] In some preferred embodiments, the inner side of the waterproof inner sheath is further provided with a wet-dry interface transition layer, which includes a shape memory polymer self-tightening sealing layer and a flexible heat insulation buffer layer arranged sequentially from the outside to the inside; a silicone oil lubricating layer is further provided between the shape memory polymer self-tightening sealing layer and the flexible heat insulation buffer layer.
[0016] In some preferred embodiments, the shape memory polymer self-shrinking sealing layer is a radiation cross-linked polyolefin heat shrink tube or a cross-linked polyurethane-based shape memory polymer tube, with a glass transition temperature of 25~35℃, a thickness of 0.8~1.5mm, and an expansion ratio of 2:1~3:1.
[0017] In some preferred embodiments, the flexible thermal insulation buffer layer is a closed-cell silicone rubber foam tape or a glass fiber reinforced silica aerogel tape. The density of the closed-cell silicone rubber foam tape is 0.25~0.40 g / cm³. 3 The closed-cell rate is ≥80%, the thermal conductivity is 0.05~0.08W / (m·K), and the thickness is 1.5~2.5mm; The glass fiber reinforced silica aerogel felt has a thermal conductivity of 0.017~0.023 W / (m·K) and a thickness of 2.0~3.0 mm.
[0018] In some preferred embodiments, a load-bearing layer is provided on the inner side of the flexible heat insulation buffer layer. The load-bearing layer is a composite woven mesh made of ultra-high molecular weight polyethylene fiber and aramid fiber, and the mass ratio of ultra-high molecular weight polyethylene fiber to aramid fiber is (60~70):(30~40).
[0019] In some preferred embodiments, the outer side of the load-bearing layer is longitudinally covered with a liquid crystal polymer film moisture-proof isolation layer, the liquid crystal polymer film having a thickness of 25~75μm, an overlap rate of ≥30%, and an axial tensile modulus of ≥10GPa.
[0020] In some preferred embodiments, the optoelectronic functional unit includes at least one electrical unit and at least one optical unit, as well as a filler material between the electrical unit and the optical unit.
[0021] By adopting the above technical solution, the dielectric adaptive air-sea trans-domain optoelectronic composite umbilical cable provided in this application has the following beneficial effects: 1. This application employs a gradient outer sheath modified with fluorosiloxanes to thermoplastic polyurethane. During extrusion molding and cooling, the thermodynamic incompatibility between the fluorosiloxane segments and the thermoplastic polyurethane matrix allows the fluorosiloxane segments to spontaneously migrate and accumulate at the melt-air interface, forming a radial gradient structure with an outer layer enriched with fluorosiloxane segments and an inner layer enriched with the thermoplastic polyurethane matrix. Based on this gradient structure, the surface energy of the outer sheath is reduced, resulting in excellent hydrophobic, oleophobic, and antifouling properties, effectively reducing marine organism attachment and water carryover on the outer surface. Simultaneously, the siloxane segments enriched in the outer layer, utilizing their non-carbon backbone structure and the formation of an inert silica layer, improve oxidation resistance, thereby enhancing the corrosion resistance of the outer sheath in salt spray environments and effectively resisting strong ultraviolet radiation and ozone erosion in air environments, delaying the aging and pulverization phenomena that occur in traditional thermoplastic polyurethane sheaths after cross-media recycling. The inner layer, enriched with thermoplastic polyurethane matrix, maintains excellent flexibility, high elasticity, and good adhesion to the underlying material. This effectively avoids the risk of increased hardness and interlayer delamination in the outer sheath caused by overall fluorosilicification, ensuring that the outer sheath does not crack due to surface hardening under complex conditions such as repeated water entry and exit, winding and deployment, thus maintaining stable sealing performance and mechanical integrity. It achieves hydrophobic and corrosion-resistant properties, resistance to UV ozone aging, and wide-temperature mechanical stability in seawater-air cross-medium environments.
[0022] 2. This application achieves functional division and synergy among the three components by setting up a reversible buoyancy control layer composed of closed-cell hollow glass microspheres, polyurethane semi-open-cell foam particles, and temperature-sensitive superabsorbent resin: The polyurethane semi-open-cell foam particles, utilizing their high open-cell ratio and good resilience, undertake the physical functions of water storage and drainage. Their open pores rapidly fill with water under static pressure upon water inflow and elastically rebound with pressure upon water outflow, providing a physical channel for reversible water inflow and outflow; the temperature-sensitive superabsorbent resin utilizes its moderately low critical temperature... The solubility temperature characteristics provide temperature-responsive chemical regulation and water-blocking functions. At low temperatures (seawater environment), it absorbs water and swells to form a localized gel plug layer, preventing water penetration inwards. At high temperatures (air environment), it swells and actively releases bound water, achieving temperature-triggered autonomous drainage. Closed-cell hollow glass microspheres, utilizing their low true density and high compressive strength, provide skeletal support and basic buoyancy. Within the applicable water depth range, they remain closed-cell and do not absorb water, providing a continuous and stable reserve of basic buoyancy and compressive support for the regulation layer. The synergistic effect of these three components allows the cable's overall density in seawater to automatically approach the density of seawater for weightless suspension, and its overall density to actively and rapidly decrease in air for use and recovery in aerial environments. This overcomes the technical shortcomings of traditional glass microsphere density regulation layers, such as unidirectional water absorption, inability to actively drain water, and increased aerial load due to residual water retention after discharge. This enhances the buoyancy adaptability and operational convenience of the umbilical cable in cross-medium missions. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the structure of a medium-adaptive air-sea cross-domain optoelectronic composite umbilical cable provided in an embodiment of this application.
[0025] The following is supplementary explanation of the attached figures: 1- Photoelectric functional unit; 2- Load-bearing layer; 3- Dry and wet interface transition layer; 4- Waterproof inner sheath; 5- Reversible buoyancy control layer; 6- Microporous permeable membrane; 7- Gradient permeable outer sheath. Detailed Implementation
[0026] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0027] The term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of this application. In the description of this application, it should be understood that the terms "upper," "lower," "top," "bottom," etc., indicating orientation or positional relationships based on the orientation or positional relationships shown in the accompanying drawings, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Moreover, the terms "first," "second," etc., are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of this application described herein can be implemented in orders other than those illustrated or described herein.
[0028] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to an integer, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included. For example, a specified range from “1 to 10” should be considered to include any and all subranges between the minimum value 1 and the maximum value 10. Exemplary subranges of the range 1 to 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, etc.
[0029] like Figure 1 As shown, this application embodiment provides a medium-adaptive air-sea cross-domain optoelectronic composite umbilical cable. The umbilical cable includes, from the inside out: optoelectronic functional unit 1, load-bearing layer 2, waterproof inner sheath 4, reversible buoyancy control layer 5, microporous water-permeable membrane 6, and gradient water-permeable outer sheath 7; preferably, a dry-wet interface transition layer 3 is also provided between the load-bearing layer 2 and the waterproof inner sheath 4.
[0030] The gradient permeable outer sheath 7 is the outermost structure of the cable body. A microporous permeable membrane 6 is attached to the inner wall of the gradient permeable outer sheath 7. A reversible buoyancy control layer 5 fills the annular cavity formed by the microporous permeable membrane 6 and the waterproof inner sheath 4. Understandably, the annular cavity can be continuous, multi-slotted, or other structural forms to achieve stable and reliable support and containment of the reversible buoyancy control layer 5; the specific structure is not limited.
[0031] The gradient permeable outer sheath 7 is a fluorosiloxane-modified thermoplastic polyurethane gradient sheath, which is made by melt reaction extrusion granulation of thermoplastic polyurethane granules, fluorosiloxane oligomers and crosslinking / grafting agents, followed by extrusion molding. During the extrusion molding and cooling process, taking advantage of the thermodynamic incompatibility between fluorosiloxane segments and thermoplastic polyurethane matrix, the fluorosiloxane segments spontaneously migrate and enrich towards the melt-air interface, forming a radial gradient structure with an outer layer enriched with fluorosiloxane segments and an inner layer enriched with thermoplastic polyurethane matrix. Based on this gradient structure, the surface energy of the outer sheath is reduced, giving it excellent hydrophobic, oleophobic, and antifouling properties. This effectively reduces marine organism attachment and water carryover on the sheath surface. Combined with the characteristics of thermoplastic polyurethane, such as the presence of pores, seawater can still penetrate under pressure. Simultaneously, the siloxane segments enriched in the outer layer utilize their non-carbon backbone structure and the formation of an inert silica layer on the surface to improve oxidation resistance, thereby enhancing the sheath's corrosion resistance in salt spray environments and effectively resisting strong ultraviolet radiation and ozone erosion in air, delaying the aging and powdering phenomena that occur in traditional thermoplastic polyurethane sheaths after cross-media recycling. The inner layer, enriched in thermoplastic polyurethane matrix, maintains good flexibility, high elasticity, and good adhesion to the underlying materials, effectively avoiding the increased hardness and interlayer delamination risks caused by overall fluorosilicification. This ensures that the outer sheath does not crack due to surface hardening under complex conditions such as repeated water entry and exit, winding and deployment, maintaining stable sealing performance and mechanical integrity. This achieves a balance between hydrophobicity and corrosion resistance, resistance to UV ozone aging, and wide-temperature mechanical stability in a seawater-air cross-medium environment. Additionally, as an option, the outer surface of the sheath can be microstructured, for example, to form a fish-scale-like biomimetic texture, thereby helping to reduce underwater navigation drag and minimize vortex-induced vibrations caused by wind loads in the air.
[0032] The reversible buoyancy control layer 5 includes closed-cell hollow glass microspheres, polyurethane semi-open-cell foam particles, and temperature-sensitive superabsorbent resin. The three components provide basic buoyancy support, physical water storage / drainage, and temperature-responsive chemical control functions, respectively, and work together to form a reversible density adjustment system to achieve adaptive density control of the cable body during the switching process between seawater and air media.
[0033] Closed-cell hollow glass microspheres serve as the rigid framework of the control layer, maintaining the integrity of the closed-cell structure without damage or water absorption within the applicable water depth range. This provides continuous basic buoyancy reserves and resists deep-water hydrostatic pressure, maintaining the structural stability of the annular cavity. Semi-open-cell polyurethane foam particles act as an elastic framework and a reversible water storage / drainage carrier. Their semi-open-cell structure rapidly fills with water under hydrostatic pressure and recovers its pore volume through high resilience upon water discharge, providing a physical channel for water drainage. Temperature-sensitive superabsorbent polymer (SAP) acts as a temperature-responsive chemical control unit, possessing a low critical dissolution temperature (LCST). At low water temperatures, SAP is in a hydrophilic swelling state, preferentially absorbing free water from the gaps between foam particles and expanding. This forms localized gel plugs filling the gaps between particles and the necks of the open pores, preventing seawater from penetrating to the four sides of the waterproof inner sheath. Simultaneously, its swelling is constrained by the foam framework and particle gaps, preventing blockage of the main drainage channels. When the ambient temperature rises above the LCST, the SAP gel network undergoes a hydrophobic transition, actively releasing bound water and triggering drainage.
[0034] Specifically, during the water entry phase, the water temperature (2~10℃) is lower than the LCST of the SAP. Under hydrostatic pressure, seawater permeates into the annular cavity through the gradient permeable outer sheath 7 and the microporous permeable membrane 6. The open pores of the polyurethane semi-open-cell foam particles are rapidly filled with water, and their density approaches that of seawater. The SAP swells and absorbs water to form a gel plug layer that blocks water and expands in volume, which helps to reduce density and minimizes the potential adverse effects of increased compression density of the polyurethane semi-open-cell foam particles. The closed-cell hollow glass microspheres remain non-absorbent. The synergy of these three factors makes the overall density of the control layer approach that of seawater, enabling the cable to achieve weightless suspension.
[0035] During the water discharge phase, the cable is recovered into the air. If the ambient temperature rises above 30°C, exceeding the SAP's LCST (Limited Time Limit), the SAP undergoes deswelling and actively releases bound water. Simultaneously, the environmental pressure is released, and the semi-open-cell polyurethane foam particles elastically rebound, restoring their pore volume and providing a rapid drainage channel for the SAP to release moisture and residual water within the pores. The moisture is discharged along the cable under the influence of gravity and centrifugal force during recovery, preventing internal water accumulation and ensuring ease of use and recovery in the air.
[0036] Therefore, the reversible buoyancy control layer 5 overcomes the shortcomings of traditional glass microsphere density control layers, such as unidirectional water absorption, inability to actively drain water, residual water retention after water discharge leading to a sudden increase in cable linear density and excessive load in the air, by combining physical water storage / drainage, temperature-responsive chemical control, and rigid skeleton buoyancy. It achieves rapid, reversible, and adaptive control of density when switching from seawater to air medium, and improves the smoothness and safety of cross-medium umbilical cables in aerial deployment and retrieval and underwater suspension operations.
[0037] In some preferred embodiments, the gradient permeable outer sheath 7 is made by melt reaction extrusion granulation of polyether thermoplastic polyurethane granules, hydroxyl-terminated fluorosilicone oil and polyisocyanate in a mass ratio of 100:5~15:0.5~2, followed by extrusion molding. The molecular weight of the hydroxyl-terminated fluorosilicone oil is 1000~5000.
[0038] Specifically, polyether-type thermoplastic polyurethane granules, hydroxyl-terminated fluorosilicone oil, and polyisocyanate are premixed in a high-speed mixer according to the above proportions to ensure uniform dispersion of the components. Subsequently, a twin-screw extruder is used for melt reaction extrusion at a temperature of approximately 170-210°C. After extrusion, granulation is performed to obtain fluorosiloxane-modified thermoplastic polyurethane granules. These modified granules are then heated and melted in an extruder and extruded into shape. During the melt flow and cooling process, due to the thermodynamic incompatibility between the fluorosiloxane segments and the thermoplastic polyurethane matrix, the fluorosiloxane segments spontaneously migrate and accumulate towards the outer surface of the sheath, thus forming a radial gradient structure with an outer layer enriched with fluorosiloxane segments and an inner layer enriched with the thermoplastic polyurethane matrix. The polyether-type thermoplastic polyurethane granules, hydroxyl-terminated fluorosilicone oil, and polyisocyanate can all be commercially available products.
[0039] In some preferred embodiments, the closed-cell hollow glass microspheres are soda-lime borosilicate-based hollow glass microspheres with a true density of 0.19~0.24 g / cm³. 3 The particle size D50 is 45~78μm, the compressive strength is ≥5.0MPa (95% retention rate), and the volume content is 25%~40% of the total volume of the reversible buoyancy control layer 5.
[0040] True density refers to the density calculated only considering the volume of the solid material in the shell of the closed-cell hollow glass microspheres. The true density of the closed-cell hollow glass microspheres selected in this application is 0.19~0.24 g / cm³. 3 With a density far lower than seawater, it provides a continuous basic buoyancy reserve for the reversible buoyancy control layer 5. The particle size D50 is controlled between 45 and 78 μm, which avoids agglomeration and weakened interfacial bonding due to increased specific surface area of excessively fine particles, while also preventing uneven filling and stress concentration caused by excessively large particles. The compressive strength ≥ 5.0 MPa (95% retention rate) is suitable for hydrostatic pressure at deep water depths, ensuring that the closed-cell hollow glass microspheres maintain their closed-cell integrity under deep water and bending / explosion conditions, without breakage or leakage. The volume content is 25% to 40%, ensuring rigid framework support and basic buoyancy while reserving sufficient elastic water storage gaps for the polyurethane semi-open-cell foam particles, preventing a decrease in the overall elasticity of the reversible buoyancy control layer 5.
[0041] The semi-open-cell polyurethane foam particles are based on a polyether-type polyurethane matrix and have a semi-open-cell structure. The pore size is 300–800 μm, the open-cell ratio is 60%–75%, and the density is 0.06–0.12 g / cm³. 3The compressive strength is ≥1.0MPa, the compression set is ≤8%, the resilience is ≥50%, and the volume content is 35%~55% of the total volume of the reversible buoyancy control layer 5. The design of the pore size and porosity ensures rapid water filling under hydrostatic pressure during water inflow and smooth drainage with elastic rebound during water outflow. The low density and high compressive strength balance lightweight and compressive strength, while the low compression set and high resilience guarantee long-term elastic recovery during repeated water inflow and outflow cycles. The 35%~55% volume content provides ample space for the main water storage / drainage function. Understandably, the remaining portion of the total volume of the reversible buoyancy control layer 5 consists of temperature-sensitive superabsorbent resin and the voids between materials.
[0042] As an optional implementation method, polyurethane semi-open-cell foam particles can be prepared using the following raw materials and processes: Polyether polyol (number average molecular weight approximately 3000-5000), water, polyether-modified silicone oil (approximately 1.5%-3.0% of the polyol mass), and nano-silica (approximately 1.0%-3.0% of the polyol mass) are mixed evenly, then polyisocyanate (isocyanate index approximately 1.05-1.15) is added, and the mixture is rapidly stirred before being poured into a mold for foaming. After foaming, the mixture is cured at approximately 60-80°C for approximately 20-40 minutes, and then crushed and sieved to obtain the final product. All of the above raw materials can be commercially available products.
[0043] The temperature-sensitive superabsorbent polymer (SAP) is a poly(N-isopropylacrylamide) crosslinked modified sodium polyacrylate superabsorbent gel with a lower critical dissolution temperature of 28-32℃, a dry particle size of 100-200μm, and a mass content of 3-8wt% of the total mass of the reversible buoyancy control layer 5. The lower critical dissolution temperature is between the low temperature of seawater (2-10℃) and the high temperature of air (≥30℃), ensuring that upon entering the water, it absorbs water and swells to form a gel plug layer to block water, and upon exiting the water, it deswells and actively releases water. The dry particle size is smaller than the pore size of the polyurethane semi-open-cell foam particles (300-800μm), allowing it to disperse between the foam particles and the neck of the pores. After swelling, the space is limited, preventing blockage of the main drainage channel. The 3-8wt% dosage ensures sufficient water absorption and water blocking capacity while avoiding excessive swelling of SAP that would occupy too much space and affect the elastic rebound and drainage efficiency of the foam particles.
[0044] In some preferred embodiments, the microporous permeable membrane 6 is a pressure-resistant composite microporous membrane, comprising an inner microporous membrane and an outer high-strength polyester fiber woven reinforcing mesh. The inner microporous membrane can be made of expanded polytetrafluoroethylene or thermoplastic polyurethane, while the outer high-strength polyester fiber woven reinforcing mesh provides structural support to improve the overall pressure resistance of the microporous permeable membrane 6.
[0045] The overall thickness of the microporous permeable membrane 6 is approximately 0.20~0.35 mm, and its hydrostatic pressure resistance is not less than 1.0 MPa. Among them, the pore size of the inner microporous membrane is approximately 0.3~2.0 μm, and the porosity is approximately 70%~80%.
[0046] When the cable is in a seawater environment, the external water pressure drives the seawater to seep into the annular cavity through the microporous permeable membrane 6; when the cable is in a normal air environment, the microporous permeable membrane 6 prevents liquid water from naturally seeping in, thus avoiding unnecessary water accumulation inside the cavity.
[0047] In some preferred embodiments, the waterproof inner sheath 4 is made of polyether-type thermoplastic polyurethane or polyethylene material, with a thickness of 0.6~1.0 mm, a Shore hardness of A85~95, and a water permeability coefficient of less than 1×10⁻⁶. -12 cm 3 ·cm / (cm 2 (·s·Pa). The waterproof inner sheath 4 is used to prevent water from penetrating inward, so as to prevent seawater from contacting the photoelectric functional unit 1 located inside it.
[0048] In some preferred embodiments, the inner wall of the annular cavity is provided with a longitudinal water guide groove extending along the cable body axis. Specifically, the longitudinal water guide groove can be provided on the outer surface of the waterproof inner sheath 4 to guide the water inside the reversible buoyancy control layer 5 to flow along the cable body axis, so as to facilitate the water to be discharged from the cable body under the action of gravity and centrifugal force.
[0049] In some preferred embodiments, the inner side of the waterproof inner sheath 4 is further provided with a wet-dry interface transition layer 3, which includes a shape memory polymer self-tightening sealing layer and a flexible thermal insulation buffer layer arranged sequentially from the outside to the inside; and a silicone oil lubricating layer is further provided between the shape memory polymer self-tightening sealing layer and the flexible thermal insulation buffer layer. The silicone oil lubricating layer is used to eliminate or reduce the shear stress generated between the layers when the shape memory polymer self-tightening sealing layer shrinks, so as to avoid obstruction of relative displacement between the layers or interface damage.
[0050] In some preferred embodiments, the shape memory polymer self-shrinking sealing layer can be made of radiation-crosslinked polyolefin heat-shrinkable tubing or crosslinked polyurethane-based shape memory polymer tubing. The radiation-crosslinked polyolefin can be further selected from crosslinked polyethylene, ethylene-vinyl acetate copolymer, or mixtures thereof. The glass transition temperature of this shape memory polymer self-shrinking sealing layer is approximately 25-35°C, its thickness is approximately 0.8-1.5 mm, and its expansion ratio (the ratio of the expanded inner diameter to the original inner diameter) is approximately 2:1-3:1. This sealing layer is directly fitted inside the reversible buoyancy control layer 5 in its expanded state, with uniform circumferential shrinkage and no overlapping gaps.
[0051] When the cable is in a deep-sea low-temperature environment (approximately 2~10℃), the sealing layer is in a glassy state, maintaining the dimensional stability after expansion, thereby maintaining the initial wrapping state of the inner structure and preventing moisture in the reversible buoyancy control layer 5 from further penetrating into the inner photoelectric functional unit 1.
[0052] When the cable body is out of the water, and the ambient temperature rises above its glass transition temperature (or is assisted by Joule heating generated by energizing the cable body), the sealing layer transforms into a highly elastic state and triggers radial shape recovery, gradually shrinking to its original diameter, forming a tight wrap around the inner structure, actively closing the micro gaps that may be caused by medium switching (such as pressure release, temperature change), thereby ensuring long-term sealing reliability during cross-medium processes.
[0053] As an alternative implementation, if the ambient temperature is insufficient to trigger shape recovery, approximately 1-3 wt% of carbon nanotubes or graphene conductive fillers can be incorporated into the shape memory polymer material. In this case, a low-voltage current (e.g., approximately 5-12V DC voltage applied through a control line) can be applied through the internal functional units of the cable to achieve electrothermal heating using the Joule heating effect, thereby triggering shape recovery in the shape memory polymer and ensuring its normal operation under any climatic conditions.
[0054] In some preferred embodiments, the flexible thermal insulation buffer layer is a closed-cell silicone rubber foam tape or a glass fiber reinforced silica aerogel tape, which is covered on the outside of the load-bearing layer 2 by longitudinal wrapping or low-tension unidirectional spiral winding.
[0055] The density of this closed-cell silicone rubber foam tape is 0.25~0.40 g / cm³. 3 The foamed tape has a closed-cell rate of ≥80%, a thermal conductivity of 0.05~0.08 W / (m·K), and a thickness of 1.5~2.5 mm. After being immersed in water, the foamed tape undergoes elastic volume compression under hydrostatic pressure, providing a buffer space for the inner structure. After being removed from the water, as the environmental pressure is released, the foamed tape recovers its original volume due to its elastic rebound characteristics, without cracking or permanent deformation.
[0056] The thermal conductivity of glass fiber reinforced silica aerogel tape is 0.017~0.023 W / (m·K), the thickness is 2.0~3.0 mm, and the overlap rate is approximately 20%~30%. This material possesses a certain degree of flexibility, allowing it to be bent and wound, and is primarily used as a static thermal insulation buffer. Its outer surface is provided with a shape memory polymer self-compressing sealing layer for mechanical protection, preventing the aerogel material from directly bearing shear stress under high pressure.
[0057] This flexible thermal insulation buffer layer provides radial temperature gradient isolation in the air, reducing the thermal shock to the inner load-bearing layer 2 and the photoelectric functional unit 1 caused by drastic temperature changes across the medium. Its longitudinal wrapping method avoids torsional stress concentration caused by helical winding and provides elastic deformation coordination space for the shape memory polymer self-tightening sealing layer to shrink. When immersed in water, the closed-cell silicone rubber foam tape is elastically compressed under hydrostatic pressure, without hindering the circumferential constraint of the shape memory polymer self-tightening sealing layer; after exiting the water, it elastically rebounds and restores its thermal insulation performance.
[0058] In some preferred embodiments, a load-bearing layer 2 is provided on the inner side of the flexible heat insulation buffer layer. The load-bearing layer 2 is a composite woven mesh made of ultra-high molecular weight polyethylene fiber and aramid fiber, and the mass ratio of ultra-high molecular weight polyethylene fiber to aramid fiber is (60~70):(30~40).
[0059] Compared to traditional galvanized steel wire armor, this composite woven mesh is resistant to seawater, UV radiation, and chemical corrosion, making it suitable for alternating medium service environments. The aramid fiber can be para-aramid, with a tensile strength of not less than 2.8 GPa and a thermal decomposition temperature of not less than 500℃, providing high-temperature dimensional stability and cut resistance. The ultra-high molecular weight polyethylene fiber has a lower density and excellent abrasion resistance, helping to reduce the overall weight of the cable.
[0060] As an optional implementation, the inner layer can be twisted in the S-direction and the outer layer in the Z-direction during the mixed weaving process, and the directions can be interchanged as needed. The weaving density of the composite braided mesh is approximately 85% to 95%. During the dynamic bending process of the cable, the relative slippage between the two types of fibers can effectively absorb kinking energy, thereby suppressing the occurrence of birdcage-like effects.
[0061] In some preferred embodiments, the outer side of the load-bearing layer 2 is longitudinally covered with a liquid crystal polymer film moisture-proof barrier layer. The thickness of this liquid crystal polymer film is approximately 25-75 μm, with an overlap ratio of not less than 30% and an axial tensile modulus of not less than 10 GPa. When the load-bearing layer 2 is subjected to tensile load, this liquid crystal polymer film moisture-proof barrier layer can provide longitudinal stress-assisted transfer, reducing stress concentration that may be caused by local fiber breakage (this liquid crystal polymer film moisture-proof barrier layer is not a primary load-bearing structure; its stress-assisted function is based on the primary load-bearing structure of the load-bearing layer 2, achieving local stress redistribution through the synergistic deformation of the high-modulus film and the load-bearing layer 2). Simultaneously, the liquid crystal polymer film moisture-proof barrier layer has extremely low water vapor permeability (less than 0.01 g / (m²)). 2 •24h), which is about two orders of magnitude lower than that of polyimide film, can serve as a second moisture barrier to provide moisture protection for the inner optoelectronic functional unit 1.
[0062] In some preferred embodiments, the optoelectronic functional unit 1 includes at least one electrical unit and at least one optical unit, as well as a filler material between the electrical unit and the optical unit.
[0063] The optical unit can use bend-resistant optical fiber, such as single-mode fiber coated with polyimide. Alternatively, the fiber coating can be a double-layer structure, with an inner flexible buffer layer (e.g., UV-cured silicone rubber, Shore hardness approximately A40-50, elastic modulus approximately 0.5-1.0 MPa) to buffer bending stress; and an outer rigid protective layer (e.g., UV-cured acrylate resin, Shore hardness approximately D65-75, elastic modulus approximately 1500-2000 MPa) to maintain the fiber's geometric stability. Furthermore, the fiber can be further encased in a buffer sheath and a high-tensile-strain thermoplastic outer layer (materials such as polyurethane or ethylene-tetrafluoroethylene copolymer, with a tensile strain of not less than 30%). Optical units with this structure are less prone to microbending losses due to sheath hardening in deep-sea high-pressure environments and can withstand smaller bending radii without easily kinking when deployed in air. It is understood that the optical unit may also adopt other types of bend-resistant optical fiber, coating structure and buffer material, as long as the above-mentioned bend resistance and compression resistance functions can be achieved. This application does not make specific limitations in this regard.
[0064] The electrical unit can adopt a structure combining a cross-linked polyethylene insulation layer and a copper-plastic composite tape wrapped shielding layer, and the conductor can be bare copper stranded wire. The copper-plastic composite tape, as a metallic shielding layer, can effectively prevent moisture from contacting the insulation layer, thereby maintaining stable electrical performance. It should be noted that the electrical unit can also use other insulating materials (such as polypropylene, ethylene-tetrafluoroethylene copolymer, etc.), other shielding structures (such as braided shielding, aluminum-plastic composite tape, etc.), or other conductor forms (such as tinned copper stranded wire, silver-plated copper stranded wire, etc.), as long as they can meet the requirements for power transmission and insulation shielding. This application does not impose specific limitations in this regard.
[0065] The space between the electrical and optical units can be filled with tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer (PFA). This material exhibits good creep resistance, chemical corrosion resistance, and wide temperature range stability (applicable temperature range approximately -196°C to +260°C). When the cable bends across the medium, this filler helps maintain the relative position stability of the functional units, preventing local electric field distortion and fiber microbending loss caused by the collapse of internal voids. It should be understood that other materials with similar creep resistance, chemical corrosion resistance, and wide temperature range stability can also be used as fillers, as long as they can maintain the relative position stability of the functional units and prevent the collapse of internal voids; this application does not impose specific limitations in this regard.
[0066] Unless otherwise specified, all the above layers can be prepared using existing methods in the art, such as extrusion molding, coating, impregnation, wrapping, braiding, and prefabrication and assembly. Specific processes can be selected based on the material properties and structural requirements of each layer, and are not specifically limited here. Those skilled in the art, with a full understanding of the above technical solutions and in conjunction with conventional techniques in the art, can realize the preparation of the umbilical cable of this application.
[0067] The following detailed description of an example of this application is exemplary and is used only to explain this application, and should not be construed as limiting this application.
[0068] Example 1: A medium-adaptive air-sea cross-domain optoelectronic composite umbilical cable, which includes, from the inside out: an optoelectronic functional unit, a load-bearing layer, a dry-wet interface transition layer, a waterproof inner sheath, a reversible buoyancy control layer, a microporous permeable membrane, and a gradient permeable outer sheath.
[0069] 1. Optoelectronic functional unit The optoelectronic functional unit includes three power conductors, one pair of control conductors, one ground conductor, and two optical units, as well as PFA filler material filling the spaces between the units.
[0070] (1) Preparation of electrical units Power conductor: Use bare copper stranded wire conforming to IEC 60228 Class 2 standard, with a stranding ratio of 12. Connect three 4mm² strands... 2 The copper conductor is insulated with cross-linked polyethylene (XLPE) extrusion insulation with a nominal thickness of 1.5 mm. After being cross-linked by electron beam irradiation, a copper-plastic composite tape shielding layer is wrapped around the insulation layer with an overlap rate of 20%.
[0071] Control conductors: Take two 1.5mm conductors. 2 Tinned copper stranded wire, with ethylene propylene rubber (EPR) based elastomer extrusion insulation (e.g., Arlanx Keltan® 5470C), 0.8mm thick, twisted into pairs and then wrapped with an aluminum-plastic composite tape shielding layer, with an overlap rate of 15%.
[0072] Grounding conductor: Use one 2.5mm wire. 2 Yellow-green bicolor bare copper stranded wire.
[0073] (2) Fabrication of optical units The optical unit uses bend-resistant fiber, specifically bend-insensitive single-mode fiber conforming to the ITU-T G.657.A2 standard (e.g., YOFC® G.657.A2 from Yangtze Optical Fibre and Cable Joint Stock Limited Company, which is fully compatible with G.652.D fiber). Key fiber parameters: mode field diameter (8.6±0.4) μm (@1310nm), cladding diameter (125.0±0.7) μm, coating diameter (200±10) μm.
[0074] The optical fiber coating adopts a double-layer structure: the inner layer is UV-curable silicone rubber, and the outer layer is UV-curable acrylic resin. The optical fiber is covered with a stainless steel buffer sleeve, and a thermoplastic polyurethane sheath is extruded over the sleeve.
[0075] (3) Optoelectronic functional unit assembly The three power conductors, one pair of control conductors, one grounding conductor, and two optical units are arranged in parallel in a centrally symmetrical manner. The units are filled with PFA filler (such as DuPont™ Teflon® PFA950HP), and then stranded into a cable using a cabling machine. The stranding pitch is 16 times the cable diameter, and the stranding direction is S. The outer layer is wrapped with polyester tape binding layer with an overlap rate of 20%, forming an optoelectronic functional unit assembly.
[0076] 2. Load-bearing layer Ultra-high molecular weight polyethylene (UHMWPE) fibers (e.g., DSM Dyneema® SK78 from the Netherlands) and aramid fibers (e.g., DuPont™ Kevlar® 49 from the United States) are mixed at a mass ratio of 65:35 and double-layered reverse weaving is performed using a 24-spindle braiding machine (the inner S-direction is UHMWPE fiber, and the outer Z-direction is aramid fiber), with a weaving density of 90%. After weaving, a liquid crystal polymer film moisture barrier layer (e.g., Kuraray Vectran® HT from Japan) is longitudinally coated on the outside, with a thickness of 50 μm, an overlap rate of 30%, and an axial tensile modulus ≥15 GPa.
[0077] 3. Dry-wet interface transition layer The dry-wet interface transition layer consists of a shape memory polymer self-tightening sealing layer and a flexible thermal insulation buffer layer from the outside to the inside, with a silicone oil lubricating layer between the two layers.
[0078] (1) Flexible thermal insulation buffer layer Select closed-cell silicone rubber foam tape (e.g., Dow Corning® Silastic® 3481 closed-cell foam tape, density 0.30 g / cm³). 3 (With a closed-cell rate of ≥85%, a thermal conductivity of 0.06 W / (m·K), and a thickness of 2.0 mm), it is wrapped around the outside of the load-bearing layer in a longitudinal wrapping manner with an overlap rate of 25%.
[0079] (2) Silicone oil lubricating layer Dimethyl silicone oil (e.g., Dow Corning® PMX-2001000cSt) is uniformly coated onto the outer surface of the flexible thermal insulation buffer layer, with a coating amount of approximately 50 g / m². 2 .
[0080] (3) Shape memory polymer self-tightening sealing layer Radiation cross-linked polyethylene heat shrink tubing (such as TE Connectivity Raychem® WCSM-50 / 20 from the United States, with an original inner diameter of 20 mm, an expanded inner diameter of 50 mm, an expansion ratio of 2.5:1, a wall thickness of 1.0 mm, and a glass transition temperature of 30°C) is selected and fitted onto the outside of the silicone oil lubricating layer in an expanded state, allowing for natural adhesion after installation.
[0081] 4. Waterproof inner sheath Polyether-type thermoplastic polyurethane (e.g., BASF Lastollan® 1195A, Shore A hardness A92) is selected and extruded into a tubular structure outside the dry-wet interface transition layer using a single-screw extruder. The extrusion temperature is 180~200℃, the die temperature is 195℃, the extrusion speed is 5m / min, the thickness is 0.8mm, and the water permeability coefficient is ≤5×10⁻⁶. -14 cm 3 ·cm / (cm 2 (·s·Pa). The longitudinal water guide groove is integrally formed on the outer surface of the waterproof inner sheath using an extrusion mold.
[0082] 5. Reversible buoyancy control layer The reversible buoyancy regulating layer is filled within the annular cavity formed by the microporous permeable membrane and the waterproof inner sheath. Its composition includes: (1) Closed-cell hollow glass microspheres Soda lime borosilicate-based hollow glass microspheres were selected (e.g., 3M™ Glass Bubble SiM16K from 3M Corporation, USA, with a true density of 0.20 g / cm³). 3 (Particle size D50 approximately 55 μm, compressive strength ≥ 50 MPa), measured at 30% by volume.
[0083] (2) Preparation of polyurethane semi-open-cell foam particles The following ingredients are added: 100 parts by weight of polyether polyol (e.g., Shandong Lanxing Dongda Chemical MN-4000, trifunctional, number average molecular weight 4000), 2.5 parts by weight of water, 2.0 parts by weight of polyether modified silicone oil pore opener (e.g., Evonik® TEGOSTAB® B8871, Germany), and fumed silica nano-coated silica (e.g., Wacker HDK® N20, Germany, specific surface area 200 m²). 2 Mix 2.0 parts by weight (g) evenly, add polymethylene polyphenyl isocyanate (e.g., Wanhua Chemical WANNATE® PM-200, isocyanate index 1.10), stir quickly for about 15~20s and then pour into a mold for free foaming; mature at 70℃ for 30min, and obtain foam particles by crushing and sieving.
[0084] The resulting particles exhibit the following properties: pore size approximately 500 μm, porosity approximately 68%, density approximately 0.08 g / cm³, compressive strength approximately 1.2 MPa, compression set approximately 6%, and resilience approximately 55%. These parameters are based on a volume content of 45%.
[0085] (3) Preparation of temperature-sensitive superabsorbent resin 7.0 g of N-isopropylacrylamide, 3.0 g of sodium acrylate, and 0.05 g of N,N'-methylenebisacrylamide were dissolved in 100 mL of deionized water. The mixture was purged with nitrogen for 30 min to remove oxygen, and then 0.05 g of ammonium persulfate was added. The reaction was carried out at 60 °C for 6 h. The product was dried, crushed, and sieved to obtain polymer particles with a dry particle size of approximately 150 μm and a lower critical dissolution temperature of approximately 30 °C. The product was measured as 5% of the total mass of the reversible buoyancy control layer.
[0086] (4) Fill The hollow glass microspheres and polyurethane semi-open-cell foam particles were premixed at a volume ratio of 2:3 and evenly sprinkled into a temperature-sensitive superabsorbent resin to obtain a reversible buoyancy control layer mixture. This mixture was then filled into the annular cavity formed by the microporous permeable membrane and the waterproof inner sheath, allowing it to accumulate naturally and be gently compacted.
[0087] 6. Microporous permeable membrane The microporous permeable membrane is a pressure-resistant composite microporous membrane, consisting of an inner microporous membrane (expanded polytetrafluoroethylene, such as Gore-Tex® ePTFEMembrane from Gore Corporation, USA, with a pore size of 1.0 μm and a porosity of 75%) and an outer high-strength polyester fiber woven reinforcing mesh (such as high-strength polyester industrial filament from Zhejiang Guxiandao Green Fiber Co., Ltd., with a linear density of 1100 dtex and a weaving density of 48×48 threads / 10cm). The overall thickness is 0.28 mm, and it can withstand hydrostatic pressure ≥1.0 MPa.
[0088] 7. Gradient-permeable outer sheath (1) Preparation of fluorosiloxane-modified thermoplastic polyurethane granules Polyether-type thermoplastic polyurethane granules (e.g., BASF Lastollan® 1185A, Shore A85), hydroxyl-terminated fluorosilicone oil (e.g., Hubei Xinlantian New Material Co., Ltd. N-3000, molecular weight 3000, hydroxyl value approximately 37 mg KOH / g), and hexamethylene diisocyanate trimer (e.g., Covestro Desmodur® N3300, NCO content approximately 22%) were premixed in a high-speed mixer at a mass ratio of 100:10:1 for 10 min. The mixture was then melt-extruded at 190°C using a co-rotating twin-screw extruder (screw speed 200 rpm, residence time approximately 2 min) to allow a mild grafting reaction between the hydroxyl-terminated fluorosilicone oil and the hydroxyl groups of the thermoplastic polyurethane. The extrudate was then underwater pelletized (water temperature 20~30°C) and dried to obtain modified granules.
[0089] (2) Sheath extrusion molding The modified granules were heated to 200°C and melted using a single-screw extruder. The granules were then extruded through an annular die onto a microporous permeable membrane to form a tubular sheath. The extrusion speed was 3 m / min and the traction speed was 3.2 m / min. After cooling in a water-cooling tank, a gradient permeable outer sheath with a wall thickness of approximately 2.0 mm was obtained.
[0090] Tests showed that the umbilical cable of Example 1 exhibited no corrosion or powdering on the sheath surface after a neutral salt spray test (35°C, 5% NaCl, 720h), and no cracking or powdering on the sheath surface after an ultraviolet aging test (UVA 340nm, light / condensation cycle, 500h). After immersion in water, the overall density of the cable approached that of seawater, enabling weightless suspension. After exiting the water, the cable density returned to below that of seawater, facilitating aerial recovery.
Claims
1. A medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable, characterized in that, From the inside out, it includes: photoelectric functional unit, load-bearing layer, waterproof inner sheath, reversible buoyancy control layer, microporous permeable membrane and gradient permeable outer sheath; The gradient permeable outer sheath is the outermost structure of the cable body; the microporous permeable membrane is attached to the inner wall of the gradient permeable outer sheath; the reversible buoyancy control layer is filled in the annular cavity formed by the microporous permeable membrane and the waterproof inner sheath. The gradient permeable outer sheath is a fluorosiloxane-modified thermoplastic polyurethane gradient sheath, which is made by melt reaction extrusion granulation of thermoplastic polyurethane granules, fluorosiloxane oligomers and crosslinking / grafting agents, followed by extrusion molding. The reversible buoyancy control layer includes closed-cell hollow glass microspheres, polyurethane semi-open-cell foam particles, and temperature-sensitive superabsorbent resin.
2. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 1, characterized in that, The gradient permeable outer sheath is made by melt reaction extrusion granulation of polyether thermoplastic polyurethane granules, hydroxyl-terminated fluorosilicone oil and polyisocyanate in a mass ratio of 100:5~15:0.5~2, followed by extrusion molding. The molecular weight of the hydroxyl-terminated fluorosilicone oil is 1000~5000.
3. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 1, characterized in that, The closed-cell hollow glass microspheres are soda-lime borosilicate-based hollow glass microspheres with a true density of 0.19~0.24 g / cm³. 3 The particle size D50 is 45~78μm, the compressive strength is ≥5.0MPa, and the volume content is 25%~40% of the total volume of the reversible buoyancy control layer; The polyurethane semi-open-cell foam particles are based on a polyether-type polyurethane matrix and have a semi-open-cell structure with a pore size of 300~800μm, an open-cell ratio of 60%~75%, and a density of 0.06~0.12g / cm³. 3 The compressive strength is ≥1.0MPa, the compression set is ≤8%, the resilience is ≥50%, and the volume content is 35%~55% of the total volume of the reversible buoyancy control layer; The temperature-sensitive superabsorbent resin is a poly(N-isopropylacrylamide) crosslinked modified sodium polyacrylate superabsorbent gel with a low critical dissolution temperature of 28-32°C, a dry particle size of 100-200 μm, and a mass content of 3-8% of the total mass of the reversible buoyancy control layer.
4. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 1, characterized in that, The microporous permeable membrane is a pressure-resistant composite microporous membrane, comprising an inner microporous membrane and an outer high-strength polyester fiber woven reinforcing mesh. The inner microporous membrane is made of expanded polytetrafluoroethylene or thermoplastic polyurethane. The overall thickness of the microporous permeable membrane is 0.20~0.35mm, and it can withstand hydrostatic pressure ≥1.0MPa. The pore size of the inner microporous membrane is 0.3~2.0μm, and the porosity is 70%~80%.
5. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 1, characterized in that, The waterproof inner sheath is made of polyether-type thermoplastic polyurethane or polyethylene material, with a thickness of 0.6~1.0mm, a Shore hardness of A85~95, and a water permeability coefficient of less than 1×10⁻⁶. -12 cm 3 ·cm / (cm 2 ·s·Pa).
6. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 1, characterized in that, The inner wall of the annular cavity is provided with a longitudinal water guide groove extending along the axial direction of the cable.
7. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 1, characterized in that, The inner side of the waterproof inner sheath is also provided with a dry-wet interface transition layer, which includes a shape memory polymer self-tightening sealing layer and a flexible heat insulation buffer layer arranged sequentially from the outside to the inside; a silicone oil lubricating layer is also provided between the shape memory polymer self-tightening sealing layer and the flexible heat insulation buffer layer.
8. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 7, characterized in that, The shape memory polymer self-shrinking sealing layer is a radiation cross-linked polyolefin heat shrink tube or a cross-linked polyurethane-based shape memory polymer tube, with a glass transition temperature of 25~35℃, a thickness of 0.8~1.5mm, and an expansion ratio of 2:1~3:
1.
9. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 7, characterized in that, The flexible heat insulation buffer layer is a closed-cell silicone rubber foam tape or a glass fiber reinforced silica aerogel tape. The density of the closed-cell silicone rubber foam tape is 0.25~0.40 g / cm³. 3 The closed-cell rate is ≥80%, the thermal conductivity is 0.05~0.08W / (m·K), and the thickness is 1.5~2.5mm; The glass fiber reinforced silica aerogel felt has a thermal conductivity of 0.017~0.023 W / (m·K) and a thickness of 2.0~3.0 mm.
10. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 7, characterized in that, The inner side of the flexible heat insulation buffer layer is provided with a load-bearing layer. The load-bearing layer is a composite woven mesh made of ultra-high molecular weight polyethylene fiber and aramid fiber. The mass ratio of ultra-high molecular weight polyethylene fiber to aramid fiber is (60~70):(30~40).
11. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 10, characterized in that, The load-bearing layer is longitudinally covered with a liquid crystal polymer film moisture-proof isolation layer. The thickness of the liquid crystal polymer film is 25~75μm, the overlap rate is ≥30%, and the axial tensile modulus is ≥10GPa.
12. The medium-adaptive air-sea trans-domain optoelectronic composite umbilical cable according to claim 1, characterized in that, The optoelectronic functional unit includes at least one electrical unit and at least one optical unit, as well as a filler material between the electrical unit and the optical unit.
Citation Information
Patent Citations
Penetration-type high-strength zero-buoyancy waterproof photoelectric composite umbilical cable
CN110120279A
Electrically conductive buoyant cable
US20130319721A1